CLEAN DEVELOPMENT OF FASHION MODEL SOLUTIONS FROM SYNTHETIC SURFACE-ACTIVE SUBSTANCES - , С. В., Ю. Н. (Municipal economy of cities. Series: «Economy science», 2013)
The process of purification of model solutions with synthetic surfactants sugar wastes.